Whether Superficial Abdominal Reflex is Affected by Subcostal Transverse Abdominal Incisions? A Prospective, Observational Early Experience - Bajaj, Jitin (J Neurosci Rural Pract, 2017)
INTRODUCTION: Superficial abdominal reflex (SAR) is an important part of the neurologic assessment. It is normally present and may be present or absent in various physiological as well as pathological conditions. The presence of an abdominal incision creates a dilemma in the mind of the clinician for it affecting this reflex. As there is no literature on this, we decided to study the effect of abdominal incisions on SAR. MATERIALS AND METHODS: It was a prospective, observational study. We evaluated the patients requiring transverse subcostal incision (range 3–12 cm) both preoperatively and postoperatively, for their abdominal reflexes. Patients with preoperative normal and symmetrical abdominal reflexes were included in the study. Postoperatively, we compared the change of SAR with the preoperative status and analyzed the data. RESULTS: A total of 94 patients underwent surgeries, out of which 54 patients came under inclusion criteria, comprising 36 males and 18 females. Subcostal transverse abdominal incisions were made for surgeries including both gastrointestinal and ventriculoperitoneal shunts. SAR was found unaffected by the incisions in all patients. CONCLUSIONS: Although the study was small, subcostal transverse abdominal incisions were not found to affect SAR.